REALITY OF GENDER RELATIONS: THE ROLE AND POSITION OF WORKERS IN THE MARITIME AND FISHERIES SECTOR - Situmeang, Widya Hasian (Jurnal Partisipatoris, 2019)
Gender relations between women and men should be in an equal situation. Unfortunately, the construction of Indonesian society, especially at the village level is still gender bias. Women tend to be in an unfavorable position, not even seen in development. this paper intends to raise the role and position of workers based on gender relations, especially in coastal and fisheries communities. The lack of gender studies in coastal communities as well as lack of attention and efforts to encourage gender equality in coastal and fisheries communities has led to higher gaps in gender relations. This paper mainly looks at how issues of gender injustice, sexual violence and inequality in accessing new technologies, especially digital technology in coastal communities. This paper is enriched with literature studies and the results of previous research and compared with legal products and agreements on gender equality. Keywords: gender, coastal, community, equality